THE ROLE AND IMPORTANCE OF PUBLIC DIPLOMACY, ROMANIA CASE STUDY IN THE CONTEXT OF INTEGRATION INTO NATO - Zavoeanu Raluca-Gabriela (European Scientific Journal, ESJ, 2013)
The end of the Cold War and the predictable structure of international relations system, until then, on one hand, and changes caused by the disappearance of the two great powers, media diversification and appearance of the new non-state actors on the stage of international relations on the other hand, have led to new forms of diplomacy as an alternative to the traditional. Contemporary international relations recorded ,under the impact of globalization, a process of resizing, states and governments interact, as well as individuals and NGOs and as a result the state monopoly has been put aside. A wide range of non-state actors influence a country's image abroad and traditional diplomacy is going through changes, while the progress of information technology offers multiple communication mechanisms. In the last part of this article I decided to analyze public diplomacy in the context of integration into NATO, primarily to highlighten the importance of public diplomacy in the practical implementation of the theory and secondly because the post-revolutionary period, Romania posted two major successes: NATO and EU integration, both of which are results of the efforts made in public diplomacy.